Partition Proceedings Vol. - 1 Expert Committee No. - 1 - Planning Commission (Planning Commission, 1947)
On February 20th, 1947, His Majesty’s Government announced their intention of transferring power in British India to Indian hands by June 1949. His Majesty's Government had hoped that it would be possible for the major parties to co-operate in the working-out of the Cabinet Mission’s Plan of May 16th, 1946, and evolve for India a Constitution acceptable to all concerned. This hope has not been fulfilled.
Planning Commission
Planning Commission